MONITORING OF EGFR MUTATIONS IN THE CIRCULATING TUMOR DNA FROM BLOOD PLASMA OF PATIENTS WITH NON-SMALL CELL LUNG CANCER - V. A. Shamanin; I. V. Karpov; P. А. Gervas; N. V. Cherdyntseva; E. I. Simolina; V. V. Kozlov; S. P. Kovalenko (Сибирский онкологический журнал)
Activating mutations of EGFR are associated with sensitivity of non-small cell lung cancer (NSCLC ) to tyrosine kinase inhibitors (TKI). Liquid biopsy using circulating cell-free tumor DNA (cfDNA) is proposed in cases when formalin fixed paraffin embedded (FFPE) tumor tissue is not available and for monitoring of EGFR status. In the study we evaluated new qPC R assay for EGFR mutations in plasma cfDNA. Sensitivity of the assay was 1 % of the mutant allele for L858R, L861Q, S768I mutations and deletions in exon 19, and 5 % of the mutant allele for G719X or T790M mutations Before surgery, mutation was detected in plasma of 4 out of 7 patients (57 %) with mutant EGFR in FFPE tumor tissue. Mutations found in cfDNA completely matched those found in tumor tissue in 2 cases. In one case with G719X and S768I mutations in FFPE tissue, only S768I was found in cfDNA. In another case, T790M was detected in plasma in addition to L858R that was present in tumor tissue. No EGFR mutations were detected in plasma DNA from 12 healthy volunteers and 13 cases of NSCLC with wt EGFR suggesting 100 % specificity of the assay. Liquid biopsy detected EGFR mutations in cfDNA in 8 of 16 cases of NSCLC with mutant EGFR being under therapy with TKI. Among them, 7 cases had mutations in liquid biopsy that matched those in tumor tissue and another case had T790M in addition to L858R. In 3 cases increased mutant allele frequency was detected 212 months before clinical progression.